Założenia etyczne Kodeksu Etyki Żywnościowej - Ujwary, Maria (Annales. Etyka w Życiu Gospodarczym, 2019)
The main point of the article is to analyze the ethical assumptions of the Codex of Food Ethics and to answer the question of whether the formalization of morality related to food is possible at all. The analyzed Codex was created in October 2013, with the participation of experts from various communities. The value that was indicated and considered to be accepted by all acceding to its use is the “good of the consumer,” although it was not clearly defined in the content of the Code. The Code does draw attention to safety, quality, trust, control, and respect of the law, however. These issues were discussed in the article. Unfortunately, due to the lack of information about the further fate of the Code, it is difficult to answer the question whether it has a chance to for practical application in the form proposed by its creators.